Pharmacokinetic and pharmacodynamic analysis of baloxavir marboxil, a novel cap-dependent endonuclease inhibitor, in a murine model of influenza virus infection. (10th October 2020) - Ando, Yoshinori; Noshi, Takeshi; Sato, Kenji; Ishibashi, Toru; Yoshida, Yuki; Hasegawa, Takahiro; Onishi, Motoyasu; Kitano, Mitsutaka; Oka, Ryoko; Kawai, Makoto; Yoshida, Ryu; Sato, Akihiko; et al.
Abstract: Background: Baloxavir acid, the active form of the orally available prodrug baloxavir marboxil, is a novel cap-dependent endonuclease inhibitor of influenza virus. Baloxavir marboxil has been shown to rapidly reduce virus titres compared with oseltamivir in clinical studies. Objectives: We investigated the relationship between pharmacokinetic (PK) parameters and antiviral activity of baloxavir acid based on virus titre reduction in lungs of infected mice. Methods: BALB/c mice infected with a sub-lethal dose of influenza A(H1N1), A(H1N1)pdm09, A(H3N2) or type B virus were treated on day 5 with oral baloxavir marboxil (0.5–50 mg/kg q12h), subcutaneous baloxavir acid (0.25–8 mg/kg/day), oseltamivir phosphate (5 or 50 eq mg/kg q12h) or other antivirals for 1 day. Lung virus titres were assessed 24 h after initial antiviral dosing. PK testing was performed at up to 24 h post-dosing of baloxavir marboxil or baloxavir acid in A/WSN/33-infected mice and the PK/pharmacodynamic (PD) relationship was evaluated for baloxavir acid. Results: Oral baloxavir marboxil administration showed dose-dependent virus titre reductions in lungs of mice infected with the different types/subtypes of influenza viruses 24 h post-dosing. Baloxavir marboxil at 15 mg/kg q12h resulted in ≥100-fold and ≥10-fold reductions in influenza A and B virus titres, respectively, compared with oseltamivir phosphate. PK/PD analysis showed that the plasma concentration at the end of the dosing interval ( C τ ) or the plasma concentration at 24 h after initial dosing ( C 24 ) was the PK parameter predicting the virus titres at 24 h post-dosing of baloxavir acid. Conclusions: PK/PD analysis of baloxavir acid based on virus titre reduction in this mouse model could be helpful in predicting and maximizing virological outcomes in clinical settings.